2016
DOI: 10.1016/j.jpainsymman.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Supportive Care Needs in U.S. Dialysis Centers and Lack of Knowledge of Available Resources to Address Them

Abstract: Dialysis professionals report significant unmet supportive care needs and barriers in their centers with only a small minority rating themselves as competently providing supportive care. There is an urgent need for education of dialysis professionals about available supportive care resources to provide quality supportive care to dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 20 publications
0
50
1
Order By: Relevance
“…Literature suggests that patients with ESRD have little access to hospice and palliative care service compared to those with cancer or chronic life-threatening illnesses, and healthcare staffs are also ill prepared for providing RSC (Berzoff, Swantkowski & Cohen, 2008; Culp et al, 2016). In a cross-sectional survey, Combs and colleagues reported that 95% of US nephrology trainees felt that it was moderately to very important to learn how to provide RSC; however, their knowledge in this field was insufficient to meet the requirements (Combs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that patients with ESRD have little access to hospice and palliative care service compared to those with cancer or chronic life-threatening illnesses, and healthcare staffs are also ill prepared for providing RSC (Berzoff, Swantkowski & Cohen, 2008; Culp et al, 2016). In a cross-sectional survey, Combs and colleagues reported that 95% of US nephrology trainees felt that it was moderately to very important to learn how to provide RSC; however, their knowledge in this field was insufficient to meet the requirements (Combs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, responding appropriately to assessments will require models of care that encourage enhanced communication and multidisciplinary assessments. Dialysis guidelines and standards of care must start addressing directly these outcomes and using these patient-centered assessments to both guide and evaluate the quality of care (67).…”
Section: Identifying Process Barriers That May Arise When Patient-cenmentioning
confidence: 99%
“…Although clinical practice guidelines on shared decision-making for dialysis initiation and withdrawal exist, how these guidelines are incorporated into practice is variable. 10,11 This is a practical guide that will help nephrology providers better incorporate advance care planning (ACP) into routine care for dialysis patients. We present a DOI: 10.1111/sdi.12667 framework for how to introduce early ACP as well as triggered ACP discussions for patients who are declining.…”
Section: Introductionmentioning
confidence: 99%